Nutrition In Improving Body Immunity as an Effort Protection of COVID-19 For Teachers of SMP Negeri 1 Perak Jombang - Suharti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Currently, almost all countries are facing an epidemic or disease caused by the SARS CoV-2 virus, which WHO agreed with the name Corona Virus Diesease abbreviated as Covid-19 (WHO, 2020). Based on the map data of the distribution of Covid-19 in Indonesia, as many as 543,975 people were confirmed infected with Covid-19, 454,879 people have recovered with a percentage of 83.6% of the total and 17,081 people died with a percentage of 3.1% of the total, while the percentage of children schools that were confirmed positive for infection were 8.8%. (Covid.go.id). Therefore, it is necessary to socialize the understanding of the importance of increasing body immunity during a pandemic like now. Outreach activities can be carried out through Community Service activities carried out at SMP Negeri 1 Perak Jombang, East Java. After the implementation of Community Service which aims to understand the importance of increasing body immunity in the pandemic era by consuming nutritious food and consuming Vitamin C regularly, this activity is carried out by providing counseling and providing vitamin C assistance in SMP Negeri 1 Perak Jombang and can be carried out by good This activity is able to increase knowledge about the importance of increasing body immunity by consuming nutritious foods for the body, and consuming vitamin C regularly.